Sharia Property Purchase Decision Without Bank: Analysis Of The Influence Of Price Factors Environment And Religiosity - Al Qorni, Galuh Finna Wais; Juliana, Juliana (Universitas Negeri Surabaya, 2020)
The increasing population in Indonesia will have an impact on the increasing need for life, one of which is the need for a home. KPR also comes with a sharia system without involving banks to meet the needs of the community in owning a house better known as Sharia Property. Therefore, the purpose of this research is to analyze whether there is an influence of price, environmental and religiosity factors on sharia property purchase decisions in Indonesia. The research method used is descriptive quantitative with technical data analysis using SEM-PLS method. The data of this research is processed from sharia property consumers in Indonesia amounting to 110 people. The results showed the price level, environmental level and religiosity level are in a high category. All of these variables have a positive influence so that it can influence sharia property purchase decisions. This research is expected to provide benefits for various parties in improving public understanding of Sharia property in order to improve development strategies in sharia property purchase decisions in Indonesia.